1996
DOI: 10.1002/art.1780390917
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor. A cytokine mediating endothelial migration in inflammatory arthritis

Abstract: Objective. Angiogenesis is an integral component of the vasculoproliferative phase of rheumatoid arthritis (RA). Recently, a heparin‐binding cytokine termed hepatocyte growth factor (HGF), or scatter factor (due to its ability to disperse cohesive epithelial colonies), was described. We conducted this study to investigate the hypothesis that this cytokine was present in the milieu of the inflamed joint, and that it contributed to the chemotaxis of endothelial cells in the synovial tissue. Methods. We examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
133
1
8

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(144 citation statements)
references
References 33 publications
2
133
1
8
Order By: Relevance
“…Although we and others have shown that HGF inhibits osteoblast differentiation [6,7] it seems clear that the effect of HGF on osteoblast differentiation is dependent on the concentration of the cytokine, and that HGF at low concentrations in fact may promote rather than inhibit osteoblastogenesis [14]. Plasma levels of HGF correlate to levels of HGF in synovial fluid, and levels of HGF are higher in synovial fluid than in serum obtained simultaneously from the same individuals [15,16]. Hence, HGF at high concentrations in the joints are more likely to act negatively on osteoblasts than HGF at the lower concentrations found in circulation.…”
Section: Discussionmentioning
confidence: 95%
“…Although we and others have shown that HGF inhibits osteoblast differentiation [6,7] it seems clear that the effect of HGF on osteoblast differentiation is dependent on the concentration of the cytokine, and that HGF at low concentrations in fact may promote rather than inhibit osteoblastogenesis [14]. Plasma levels of HGF correlate to levels of HGF in synovial fluid, and levels of HGF are higher in synovial fluid than in serum obtained simultaneously from the same individuals [15,16]. Hence, HGF at high concentrations in the joints are more likely to act negatively on osteoblasts than HGF at the lower concentrations found in circulation.…”
Section: Discussionmentioning
confidence: 95%
“…At the same time in other studies [7,8], a protein selectively mitogenic for vascular endothelial cells was purified from cell culture, and this protein turned out to be the same substance that induces vascular permeability-enhancing activity. VEGF is chemotactic for endothelial cells [9] and enhances their collagenase [10] and urokinase receptor expression [11]. The existence of multiple activities embodied in the same protein suggests that VEGF may play multifunctional roles both in the development of vasculature and in the maintenance of vascular structure and function.…”
mentioning
confidence: 99%
“…Of note, we have disclosed that the expression of VEGFR-2/KDR mRNA in RA bone marrow CD34+ cells was significantly higher than that in OA bone marrow CD34+ cells (Hirohata & Yanagida et al,2004). It is therefore likely that the differences in VEGF/KDR vascular activation in bone marrow CD34+ cells might result in differences in their capacity to generate endothelial progenitor cells between RA and OA patients (Koch et al,1994;Giatromanolaki et al,2001). It has been shown that decreased numbers and impaired function of endothelial progenitor cells (EPCs) resulting in defective vasculogenesis are associated with RA, leading to premature atherosclerosis (Herbrig et al, 2006;Pakozdi et al, 2009).…”
Section: Wwwintechopencommentioning
confidence: 78%